FAULT SYSTEMS IN THE UPPER CRUST OF THE FENNOSCANDIAN SHIELD, THE EAST EUROPEAN PLATFORM - V. S. Burtman; S. Yu. Kolodyazhny (Геодинамика и тектонофизика)
Directions of 683 faults located in the southeastern part of the Fennoscandian (Baltic) shield were statistically analyzed, and three orthogonal associations of fault systems were identified in the study area. According to the dynamic analysis of the fault systems and their associations, the main NW-striking faults belong to the fault network originating mainly from the early Paleoproterozoic. These faults functioned in the Paleoproterozoic during four main deformation stages: D1 – sinistral shear transtension and asymmetric rift genesis (2.1–1.9 Ga); D2 – sinistral shear transpression under oblique accretion and convergence (1.9 Ga); D3 – sinistral shear transpression under oblique collision (1.89–1.80 Ga); D4 – dextral strike-slip displacements at the background of complex escape tectonics of the late collision stage (1.80–1.78 Ga). The regional stress field changed as follows: D1 – northeast- or east-trending extension; D2 – northeast compression; D3 – sub-latitudinal compression; D4 – sub-meridian compression. Changes in dynamic loading conditions led to multiple kinematic inversions of the fault networks. Widespread transtension and transpression settings in the southeastern parts of the Baltic Shield give evidence of asymmetric rifting, oblique accretion and collision in the Paleoproterozoic, which must be taken in to account in geodynamic reconstructions.